Nanomedicines in the Management of Alzheimer’s Disease: Current View and Future Prospects - Chopra, Hitesh; Bibi, Shabana; Singh, Inderbir; Kamal, Mohammad Amjad; Islam, Fahadul; Alhumaydhi, Fahad A.; Emran, Talha Bin; Cavalu, Simona (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is a kind of dementia that creates serious challenges for sufferers' memory, thinking, and behavior. It commonly targeting the aging population and decay the brain cells, despite attempts have been performed to enhance AD diagnostic and therapeutic techniques. Hence, AD remains incurable owing to its complex and multifactorial consequences and still there is lack of appropriate diagnostics/therapeutics option for this severe brain disorder. Therefore, nanotechnology is currently bringing new tools and insights to improve the previous knowledge of AD and ultimately may provide a novel treatment option and a ray of hope to AD patients. Here in this review, we highlighted the nanotechnologies-based findings for Alzheimer's disease, in both diagnostic and therapeutic aspects and explained how advances in the field of nanotechnology/nanomedicine could enhance patient prognosis and quality of life. It is highly expected these emerging technologies could bring a research-based revolution in the field of neurodegenerative disorders and may assist their clinical experiments and develop an efficacious drug for AD also. The main aim of review is to showcase readers the recent advances in nanotechnology-based approaches for treatment and diagnosing of AD.